METHODOLOGY FRAMEWORK FOR PROCESS INTEGRATION AND SERVICE MANAGEMENT - Galinec, Darko; Vidović, Slavko (Journal of Information and Organizational Sciences, 2007)
History of information systems development was driven by business system's functions automation and mergers and acquisitions - business subjects integration into a whole. Modern business requires business processes integration through their dynamics and thus enterprise application integration (EAI) as well. In this connection it is necessary to find ways and means of application integration and interaction in a consistent and reliable way. The real-time enterprise (RTE) monitors, captures and analyzes root causes and overt events that are critical to its success the instant those events occur [6]. EAI is determined by business needs and business requirements. It must be based on business process repository and models, business integration methodology (BIM) and information flow as well. Decisions concerning technology must be in function of successful application integration. In this paper EAI methodological framework and technological concepts for its achievements are introduced.